A jigsaw guide to making sense of the world - McLellan, Alex, 1968- (IVP Books, 2012)
McLellan explores competing views of truth and belief and examines the nature of doubt. Ultimately Christianity is reasonable because it resonates with how we see and experience the world. Even if we don't have absolute certainty, we have enough to go on to have confidence in the Christian worldview. --from publisher description.